Analysis of Competitiveness and Efficiency the Export of Essential Oils from Indonesia - Rahmatun Nisa,; Tony Irawan,; Widyastutik, (International Journal of Scientific Research in Science and Technology, 2024)
This study analyzes the competitiveness, efficiency, and factors influencing Indonesia's essential oils exports using the Stochastic Frontier Gravity Model (SFGM). The main variables examined include Gross Domestic Product (GDP), Revealed Comparative Advantage (RCA), population, exchange rate, and geographical distance. The findings indicate that Indonesian essential oils are highly competitive in international markets, particularly in France, Spain, and Switzerland. Significant factors affecting export value include the real GDP of the destination country, RCA, population, exchange rate, and geographical distance. Additionally, inefficiency factors are influenced by area, language, business freedom, investment freedom, and financial freedom. Export efficiency is categorized into five levels. This study provides empirical insights into the impact of economic and non-economic factors on the export performance of Indonesian essential oils, offering valuable implications for policymakers and industry stakeholders to enhance global competitiveness and efficiency.
Keywords: Competitiveness; Efficiency; Essential Oil Exports; Stochastic Frontier Gravity Model; Indonesia